Highly efficient layer-by-layer large-scale manufacturing of polymer solar cells with minimized device-to-device variations by employing benzothiadiazole-based solid additives. Issue 38 (12th September 2022) - Oh, Jiyeon; Jung, Sungwoo; Kang, So-Huei; Park, Geunhyung; Jeong, Mingyu; Kim, Seoyoung; Lee, Seunglok; Kim, Wonjun; Lee, Byongkyu; Lee, Sang Myeon; Yang, Changduk
Abstract : Benzothiadiazole-based solid additives have been designed as morphology controllers leading to enhanced power conversion efficiency and reduced device-to-device variations in small- and large-areas single cells. Abstract : The layer-by-layer (LBL) processing approach has recently been under intensive investigation to fabricate efficient polymer solar cells (PSCs) reconsidering its many positive aspects over the bulk-heterojunction configuration. Moreover, with recently reported successful solid additives as morphology controllers, they are becoming key elements for high-performance PSCs; however, their application in LBL systems has been scarce. Herein, we carry out a comprehensive investigation into the effect of benzothiadiazole (BT) and its fluorinated analogs (FBT and 2FBT) as solid additives on the device performance of a PM6/Y6-based LBL platform. The use of FBT in the PM6 donor layer results in a suitable morphology that ensures efficient charge transport/generation properties and suppresses recombination loss, boosting the photovoltaic performance of the LBL device. These intriguing results prompt us to further study the FBT treatment in other LBL systems (PTQ10/Y6 and PM6/BTP-eC9), leading to a considerable efficiency of up to 17.71% with low inevitable convolution arising from the molecular weight variations of the used polymers. Besides, we also demonstrate efficient large-area FBT-processed LBL PSCs (efficiencies of 16.10% (0.92 cm 2 ) and 10.93% (2.50 cm 2 )) with high device reproducibility. This study is not only invaluable in shaping our understanding of LBL PSCs, but also provides the possibility of overcoming their device-to-device variations in both small- and large-area single cells.